Incidence of persistent postoperative pain after thoracotomy in a cancer hospital: a prospective, observational study - Pires, Marta; Cunha, Ana Sofia; Serafino, Sara; Marcelino, Margarida; Armada, Cláudia; Carvalho, Susana; Saraiva, Amélia (Journal of the Portuguese Society of Anesthesiology, 2023)
Background After thoracotomy, persistent postoperative pain can affect 35-57% of patients at 3 months and acute postoperative pain appears to be one of the strongest predictors of chronic pain after thoracic surgery. The aim of this study was to determine the incidence of post-thoracotomy pain at 3 months with a standardized outpatient analgesic regimen and regular pain assessment. Methods This prospective and observational study included adult patients submitted to thoracotomy between January 2018 and March 2020. Static, dynamic and neuropathic pain were assessed pre-operatively, at discharge, and at 1, 2 and 3 months after surgery. All patients received paracetamol 1g q8h, tramadol 50 mg q8h, ibuprofen 400 mg q8h, and orodispersible tramadol 50 mg PRN. Ibuprofen was maintained for 7 to 10 days and, if contraindicated, metamizole magnesium 575 mg q8h was prescribed. For neuropathic pain, pregabalin 50 mg q12h was added. Readjustments were made at 1, 2 and 3 months, according to analgesic needs. Results 69 patients were included and 55 finished the study. At 3 months, 14.5% (95% CI, 6.9%-27.2%) had dynamic numerical pain score > 3 and 12.7% (95% CI, 5.7%-25.1%) had neuropathic pain. 61.8%, 27.3% and 18.2% required pain medication at 1, 2 and 3 months, respectively. Only 7.2% had an analgesic regimen with tramadol at 3 months. Conclusion Our results suggest that a simple follow-up with effective acute pain control might have a positive clinical impact on the course of persistent post-thoracotomy pain and encourage further research.